Malignant transformation evidences of Oral Lichen Planus: When the time is of the essence. (May 2020) - Zotti, Francesca; Nocini, Riccardo; Capocasale, Giorgia; Fior, Andrea; Peretti, Martina; Albanese, Massimo
Abstract: Oral Lichen Planus (OLP) is an inflammatory chronic disease, its potential of malignant transformation is widely known, especially for lesions affecting mucosa. This letter aims to highlight, thanks to results obtained from a long-term observation of one hundred patient suffering from OLP, the importance to set proper and sufficiently long follow-ups. An important evidence observed is the malignant developing after 4 years of observation in 4 cases of 8. This leads to conclude that follow-up for OLP lesions is required to be as long as possible in order to timeously intercept malignant transformations of these lesions and to perform a realistic early diagnosis. Final suggestion is to design more prospective studies based of long observation period.